Development of Android-Based Mathematics Learning Game on the Topic of Congruence and Similarity - Qohar, Abd.; Susiswo, Susiswo; Nasution, Syaiful Hamzah; Wahyuningsih, Sapti (International Journal of Interactive Mobile Technologies (iJIM), 2021)
In general, students’ math skills in Indonesia are low. An effort must be made to get students to enjoy learning mathematics so that their mathematical abilities improve. The rapid development of smartphone technology provides an opportunity for use in mathematics learning. This study aims to develop an Android-based mathematics learning game for junior high school students on the topic of congruence and similarity. The research method used in this study is the Plomp development method with three stages: preliminary research, the prototyping stage, and the assessment phase. The subjects of this study were 56 seventh-grade students from the State Junior High School (SMPN 1) Wagir Malang. Six students participated in small group trials and 50 students participated in field trials. The results showed that the Android-based learning game on the topic of congruence and similarity had been successfully developed. The game media have been validated by experts with a score of 3.36, which shows that the media created are valid. The practicality tests in the small group trial resulted in a score of 3.50, while the field trial resulted in a score of 3.51. The effectiveness tests carried out in the small group trial resulted in a score of 3.36, while the field trial results had a score of 3.38. These results indicate that the learning games developed are practical and effective for use in mathematics learning.